2023
DOI: 10.1021/jacs.3c09494
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of Nanoions in Aqueous Solutions

Philipp Dullinger,
Dominik Horinek

Abstract: In recent years it has been increasingly recognized that different classes of large ions with multiple valency have effects conceptually similar to weakly solvated ions in the Hofmeister series, also labeled by the term chaotropic. The term “superchaotropic effect” has been coined because these effects are much more strongly pronounced for nanometer-sized ions, whose adsorption properties often resemble typical surfactants. Despite this growing interest in these nanometer-sized ions, a simple conceptual extens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Their mechanism of action is based on charge delocalization, which is responsible for their ability to disrupt the water solvation shell of the analytes and introduce chaos into the organized ionic solution. The disruption of the solvation shells of the analytes not only exposes their more hydrophobic parts to interactions with the side chains of the stationary phase, thereby increasing retention, but also counteracts the role of the shells in suppressing interactions with the stationary phase, which otherwise leads to rapid elution [35]. In particular, employing chaotropic ions is advantageous for analyzing analytes that incorporate a nitrogen atom (primary, secondary, or tertiary) within their molecular structure, particularly in cases where the analytes exhibit the characteristics of weakly basic compounds.…”
Section: Advancing Pralidoxime Separation Using Chaotropic Salt As a ...mentioning
confidence: 99%
“…Their mechanism of action is based on charge delocalization, which is responsible for their ability to disrupt the water solvation shell of the analytes and introduce chaos into the organized ionic solution. The disruption of the solvation shells of the analytes not only exposes their more hydrophobic parts to interactions with the side chains of the stationary phase, thereby increasing retention, but also counteracts the role of the shells in suppressing interactions with the stationary phase, which otherwise leads to rapid elution [35]. In particular, employing chaotropic ions is advantageous for analyzing analytes that incorporate a nitrogen atom (primary, secondary, or tertiary) within their molecular structure, particularly in cases where the analytes exhibit the characteristics of weakly basic compounds.…”
Section: Advancing Pralidoxime Separation Using Chaotropic Salt As a ...mentioning
confidence: 99%
“…Low charge-density nanoions are thus also called superchaotropes because the observed effects are orders of magnitude larger than those caused by classical chaotropic Hofmeister ions, like I – or SCN – . Overall, charge density of the ions is a key factor dictating the superchaotropic behavior of POMs and nanoions; the lower the charge density, the more prominent the super chaotropic behavior, and in turn, the stronger the binding . These characteristics lead to a wide range of applications, including foam stabilization, cross-linking gel formulations, and biological uses as membrane carriers. ,, Besides, Hohenschutz et al showed that not only POMs, but also ionic boron clusters and organic hydrophobic ions, such as tetraphenyl borate, with low charge density showed a superchaotropic effect .…”
Section: Introductionmentioning
confidence: 99%
“…The peculiar properties of superchaotropic clusters are related to strong dehydration effects and dispersion interactions of these large, charge‐delocalized anions [6,13,21–25] . Due to their high boron content, bulky size, special 3D aromaticity, [26] and biocompatibility, [27] closo ‐borates have been developed as enabling chemical tools for biology and biomedicine [28–32] .…”
Section: Introductionmentioning
confidence: 99%